The Impact of Oxytocin Massage with Lemongrass Leaf Massage Oil and Aromatherapy of Biliting Oil on Breast Milk Production - Atik Purwandari; Sjenny Tuju; Sandra Tombokan (JURNAL INFO KESEHATAN, 2025)
One of the main problems experienced by breastfeeding mothers is insufficient breast milk production. Oxytocin massage with lemongrass aromatherapy is a solution to increase breast milk production. This study aims to measure the effectiveness of oxytocin massage using Lemongrass Leaf Massage Oil and Aromatherapy of Biliting oil using on breast milk production in breastfeeding mothers. This research method is a quasi-experiment with a one group design with pre-test and post-test design. The population in this study were breastfeeding mothers who had babies aged 0-2 years as many as 30 people. The sampling technique was accidental sampling. Data processing was carried out univariately and bivariately, using the Wilcoxon Signed-Rank Test and SPSS. This study uses a nonparameric test with Wilcoxon Signed-Rank Test analysis with non-normally distributed data. The sample data scale is a ratio scale. Data collection was conducted at PMB Yulin, Tomohon City using observation sheets and measuring cups from April to September 2024. Breast milk production was measured during the Pre-test before Oxytocin Massage was carried out using Lemongrass Leaf Massage Oil and Aromatherapy of Biliting oil for 3 days, 2 times a day, morning and evening, after that in the Post-test breast milk production was measured again with a measuring cup by means of after 1 hour the mother breastfeeds by manually expressing the right and left breasts for 5 minutes. The stages of the study were the preparation, implementation, monitoring and evaluation stages. The results of the study showed the Wilcoxon P Value Statistical Test of 0.000 <0.050. Breast milk production was measured using a breast measuring cup before and after oxytocin massage where breast milk production <10 ml = 28 people (93.3%) and> 10 ml = 2 people (6.7%) and after oxytocin massage production <10 cc = 0 and> 10 cc. After the massage, there was an increase in breast milk production of 26.03. The results of the study showed that oxytocin massage with Lemongrass Leaf Massage Oil and Aromatherapy of Biliting oil on breast milk production was effective in increasing breast milk production.